The Role of Financial Innovation on Financial Development in the Case of Norway - Hosseini, Seyed Danyal (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
This thesis investigates the long-run equilibrium relationship and short-run relationship between gross domestic product, inflation, foreign direct investment, stock market traded, financial innovation, and financial development in the case of Norway between 1989 and 2018. In this thesis, the main aim is to find out the effect of financial innovation in the long-run and short-run on financial sector development. Level relationship between variables in this study confirmed by bounds test under the ARDL model mechanism. ECM under the ARDL approach used for the short-run and indicated that financial development converges to long-run equilibrium level by 48.61% speed of adjustment by the contribution of gross domestic product, inflation, foreign direct investment, stock market traded, and financial innovation every year. Results of ARDL estimation indicated that financial innovation has an inelastic, positive, and significant effect on financial development in the long-run and has a significant and negative effect in the short-run. Furthermore, the gross domestic product has a positive effect, and inflation and stock traded value have a negative effect on the financial sector development in the long-run. The Toda-Yamamoto causality test results indicate that there is a bidirectional relationship between financial innovation and financial development. Keywords: Financial Innovation, Financial Development, Toda-Yamamoto Causality Test, ARDL Approach, Norway.

ÖZ: Bu çalışma, 1989-2018 yılları arasında Norveç örneği ile gayri safi yurtiçi hasıla, enflasyon, doğrudan yabancı yatırım, hisse senedi piyasası, finansal yenilik ve finansal gelişme arasındaki uzun dönemli denge ilişkisini ve kısa dönemli ilişkiyi araştırmaktadır. Bu çalışmanın temel amacı, uzun dönemde ve kısa dönemde finansal yeniliğin finansal sektör gelişimi üzerindeki etkisini ortaya koymaktır. Bu çalışmada değişkenler arasındaki seviye ilişkisi, ARDL model (Gecikmesi Dağıtılmış Otoregresif Model) mekanizması altında sınır testi ile doğrulanmıştır. ARDL yaklaşımı altında kullanılan Hata düzeltme modeli (ECM) belirtilen finansal gelişmeyi; gayri safi yurtiçi hasıla, enflasyon, doğrudan yabancı yatırım, hisse senedi piyasası ve finansal yeniliğin katkısıyla uzun dönemli denge seviyesine % 48,61 oranında bir uyum hızına yaklaşmaktadır. (yıl). ARDL tahmin sonuçları, finansal yeniliğin uzun dönemde finansal gelişme üzerinde esnek olmayan, pozitif ve anlamlı bir etkiye sahip olduğunu ve kısa dönemde finansal sektör gelişimi üzerinde anlamlı ve olumsuz bir etkiye sahip olduğunu göstermiştir. Ayrıca, uzun dönemli denge ilişkisinde gayri safi yurtiçi hasıla finansal sektör gelişimi üzerinde olumlu bir etkiye sahipken, enflasyon ve hisse senedi işlem değeri ise olumsuz bir etkiye sahiptir. Bu çalışmada doğrudan yabancı yatırımlar uzun dönemde anlamsız bir katsayıya sahiptir. Toda-Yamamoto nedensellik testi sonuçları, finansal yenilik ve finansal gelişme arasında çift yönlü bir ilişki olduğunu göstermektedir. Anahtar Kelimeler: Finansal Yenilik, Finansal Gelişme, Toda-Yamamoto Nedensellik Testi, ARDL Yaklaşımı, Norveç.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2020. Supervisor: Assist. Prof. Dr. Nigar Taşpınar.
Keywords: Banking and Finance; Economic Conditions and Development--Norway; Financial Innovation; Financial Development; Toda-Yamamoto Causality Test; ARDL Approach; Norway